Student Motivation in Completing Arabic Assignments Using Computer and Paper-Based Assessment Methods: Comparative Study - Adra Salsabillah; Lailatul Mauludiyah; Mochammad Firdaus (Universitas Islam Negeri Palangka Raya, 2023)
Teachers use many methods to measure students' progress in learning Arabic, either by using a computer or manually. This study aimed to determine the level and comparison between student motivation to complete assignments using computer-based and paper-based test methods in Arabic language learning. This research used a quantitative approach with comparative descriptive by performing observation, questionnaire, and interview for data collection. It used data analysis methods, such as validity tests, reliability tests and percentage analysis. The research subjects were 23 tenth graders of Visual Communication Design of SMK Muhammadiyah 2 Malang. The results of this study are: (1) the motivation of students to complete Arabic language assignments by computer-based test methods is 81.13% with high category. (2) The motivation of students to complete Arabic language assignments by paper-based test method is 83.82% with high category. (3) Comparison between the motivation of students to complete assignments using computer and paper-based test methods is 2.7% with low category. This difference is due to several factors, including human resource factors. This research has contributed to the Arabic language learning evaluation as it can be used as a teacher's consideration on what methods to use.